Effects of two different peptides on pentylenetetrazole-induced seizures in larval zebrafish - Jhonathan Angel Araujo Fernández; Thatiane Cristina de Moura; Sabela Fernández Vila; Juan Andrés Rubiolo Gaytán; Iñaki López-Díaz; Soraya Learte-Aymamí; M. Eugenio Vázquez; Maria D. Mayán; Laura Sánchez; Claudia Vianna Maurer-Morelli (PLoS ONE, 2025)
Epilepsy is a common and severe neurological disease characterized by spontaneous and recurrent seizures. Although anti-seizure treatments are effective for most patients, approximately 30% remain pharmacoresistant. Moreover, uncontrolled seizures are associated with increased health risks and shortened life expectancy in individuals with refractory epilepsy. Preclinical studies play a crucial role in drug discovery, and the zebrafish (Danio rerio) have been successfully employed for this purpose. In this study, we utilized the zebrafish PTZ-induced seizure model to evaluate the effects of two peptides on seizure responses: Tripeptide (p-BTX-I) and the CX2 (a Cx43derivated peptide). Zebrafish larvae at 6 days post-fertilization were pre-treated with these peptides at various concentrations, depending on their experimental groups, 24h prior to seizure induction. We assessed seizure frequency, quantified swimming activity, measured transcript levels of genes related to inflammation and apoptosis (il1b, tnfa, cox1, cox2a, il6, casp3a, casp9, baxa, bcl2a, and c-fos), and analyzed the biodistribution of both peptides. Our results indicate that the Tripeptide exhibited anti-inflammatory and anti-apoptotic effects, particularly through reducing the expression of il1b and casp9. CX2 pre-treatment significantly downregulated inflammatory markers (il1b, il6, tnfa, and cox1). Biodistribution analysis confirmed that the CX2 peptide reached the zebrafish brain, suggesting a direct role in modulating seizure-related pathways. Our findings demonstrate that Tripeptide and CX2 peptides can modulate gene expression and mitigate molecular response associated with epileptic seizures in the zebrafish brain. These peptides thus represent promising candidates for future research aimed at developing novel anti-epileptic therapies. However, additional studies are required to evaluate their long-term efficacy, elucidate underlying mechanisms of action, and explore potential translational applications.